Triage skill and associated factors among emergency nurses in Addis Ababa, Ethiopia 2017: a cross-sectional study - Kerie, Sitotaw (BMC Res Notes, 2018)
OBJECTIVE: The aim of this study was to assess levels of triage skill and associated factors among emergency nurses in Addis Ababa, Ethiopia, 2017. RESULTS: Above half of the participants (52.9%) had a moderate level of triage skill. A strong positive relationship was found between nurses’ level of triage knowledge and skill (r = .68, p .01). Knowledge about triage, educational level and training experience had a significant relationship with triage skill with (B = 1.09, CI (1.41, 1.77), p = .002), (B = − 19.96, CI (− 30.208, − 9.715), p = .001), (B = .55, CI .16, .94), p = .006) respectively. This study revealed that most triage nurses had a moderate level of skills. Therefore, the ministry of health and hospitals should provide training and education to improve triage skill. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3769-8) contains supplementary material, which is available to authorized users.